A comparative study on the preparation methods and properties of coal‐based fluorescent carbon nanoparticles. (24th November 2019) - Awati, Abuduheiremu; Maimaiti, Halidan; Xu, Bo; Wang, Shixin
Abstract : Fluorescent carbon nanoparticles (FCNPs) have broad application prospects in the fields of bioimaging, ion detection, and photocatalysis. In this paper, coal‐based FCNPs were prepared by using mixed acid oxidation, hydrogen peroxide etching, and organic solvent extraction methods (marked as FCNPs‐AO, FCNPs‐HE, and FCNPs‐OS, respectively), and the structures and properties of the as‐prepared products were compared. It was found that the coal‐based FCNPs obtained by three kinds of methods are all aromatic structural nanomaterials linked with oxygen‐containing groups. Among them, FCNPs‐AO is a kind of hollow annular spherical particles and FCNPs‐HE and FCNPs‐OS are solid spherical particles. These FCNPs not only have similar fluorescence properties as traditional quantum dots, but also can be photoexcited to generate photogenerated electrons and holes, and it can also suppress the recombination of photogenerated electrons and holes by using its own surface defects. In particular, the electron transport capability of the FCNPs‐AO is stronger than that of FCNPs‐HE and FCNPs‐OS because of its lower charge transfer impedance, so it can be excited to generate more photogenerated electrons and has the best photogenerated carrier separation efficiency.